1994
DOI: 10.1093/bja/73.2.180
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of hypothermia during hip surgery: effect of passive compared with active skin surface warming

Abstract: We have measured aural canal (core) and skin temperatures, and body heat content in 45 patients undergoing elective hip arthroplasty. They received general anaesthesia which included thiopentone, vecuronium and enflurane and nitrous oxide in oxygen. Patients were allocated randomly to three groups: group 1, control (n = 15), received no intraoperative warming device; group 2 had passive skin surface warming (metallized plastic sheet, Thermolite (n = 15); and group 3 had active skin surface warming (forced heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 11 publications
0
27
0
3
Order By: Relevance
“…This is the most commonly tested body warming modality and is unsurprisingly associated with significantly higher postoperative core temperatures when compared with patient control groups where no warming was used [41][42][43]. The dual benefit of transferring heat to the body and reducing heat losses [44] from the skin under the air warmer accounts for this finding.…”
Section: Forced-air Warmersmentioning
confidence: 99%
“…This is the most commonly tested body warming modality and is unsurprisingly associated with significantly higher postoperative core temperatures when compared with patient control groups where no warming was used [41][42][43]. The dual benefit of transferring heat to the body and reducing heat losses [44] from the skin under the air warmer accounts for this finding.…”
Section: Forced-air Warmersmentioning
confidence: 99%
“…7 Core temperatures and body heat content decreased significantly in the reflective insulation and control groups, while the Bair Hugger Ò patients maintained thermal homeostasis. In the Bennett study, the patient population and use of the Bair Hugger Ò were similar to ours in that general anesthesia was administered, an upper body Bair Hugger Ò was used (set at 43°C), ambient temperature fluids were infused, and the patients were placed in the supine position.…”
Section: Methodsmentioning
confidence: 88%
“…The addition of more layers or the use of warmed blankets does not, unfortunately, increase the benefit proportionally [106] . Reflective insulation materials are not more efficient compared to standard drapes [4,6,13,17,92,108] . The recent improvements made in clothing for outdoor activities indicate that technological advances in drapes and blankets for hospital use must be possible [15] .…”
Section: External Warming Methods Insulationmentioning
confidence: 99%
“…Without active perioperative warming, the majority of surgical patients will become at least slightly hypothermic (core temperature < 36 ° C) [4] . Torossian et al reported a survey on thermomanagement in 316 European hospitals that on a certain day during 8083 surgical procedures, only in 19 % of the patients was body temperature monitored, and only 38 % were actively warmed [118] .…”
Section: Incidence Of Perioperative Hypothermiamentioning
confidence: 99%